Development and Utilization of Online Teacher Professional Development Program to Improve Private e-Tutors’ TPACK Skills - Benedicto, Maristhel Tradio; Sala, Ana Marie Villacarillo; Carascal, Ivy Coronado; Mutya, Romel Cayao (FKIP Universitas Lampung, 2023)
Development and Utilization of Online Teacher Professional Development on Private E-Tutors’ TPACK Skills. Objective: The study aimed to design, implement, and evaluate an online teacher professional development training program and develop the TPACK skills of private e-tutors as evidenced by their lesson design and teaching demonstration performance. Methods: A mixed method in data gathering such as TPACK survey, pre-post-performance, and feedbacking was utilized. The input-process-output method with the PRIME framework in the process stage was used. The training program design was evaluated by experts anchored with the frameworks and theories with the synchronous form of learning for 20 contact hours. Findings: Findings revealed a significant mean gain between the pre-post-performance of the teachers’ lesson design and teaching demonstration. Conclusion: The online teacher professional development training program developed and enhanced the teachers’ TPACK skills. The study proposed guidelines for conducting oTPD training programs and compilation of lesson designs based on the TPACK framework. Keywords: e-tutors, online teaching , professional development, TPACK.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202345